Examen especial aplicado a la cuenta de ingresos como medio de verificación del cumplimiento de la normativa en el Gobierno Autónomo Descentralizado del cantón Valencia del año 2014 - Cando Segovia, Ángel Arturo (2016)
The project was developed in the Decentralized Autonomous Government of Valencia Canton, located in av. December 13th and August 2nd street in front of the central park of Valencia Canton. In order to mitigate the errors in the control processes and the implementation of internal control standards and at the same time corrected this way the actions of the involved officials in raising revenues generated in the public entity. The study focused on use of the deductive method that yielded conclusions made based on particular facts, to establish general conclusions; the inductive method; allowed to conduct a comprehensive study of the income generated in the Autonomous Government Decentralized Municipal Valencia Canton, the information obtained will be through observation and interviews, same that will be used to draw conclusions and suggestions and finally the synthetic analytical method; It was used to achieve differentiate and analyze the processes carried out by the Autonomous Decentralized Municipal Government of Valencia Canton to raise a proposed solution to the problem and make conclusions about the effectiveness during the recording of income. Breach of the rule 403-01, 403-02, 403-03, 403-04 and 403-11. Research improves existing shortcomings in the implementation of the processes adopted by officials during the collection of revenue that raises cash and determines the degree of non-compliance with internal control standards. Keywords: income, regulation, control, mitigate, raises